2015
DOI: 10.5696/i2156-9614-5-8.19
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metals Speciation and Human Health Risk Assessment at an Illegal Gold Mining Site in Igun, Osun State, Nigeria

Abstract: Metals such as lead (Pb), cadmium (Cd), mercury (Hg), zinc (Zn), and chromium (Cr) are known for their persistent behavior in the environment with consequent environmental, human and animal damage. 1,2 Some of these metals are known to act as human mutagens and carcinogens and are associated with various human ailments such as cardiovascular, nervous system, blood and bone diseases, kidney failure, gingivitis, and tremors, among others. 3,4 These metals are easily released into the environment via anthropogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
23
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 31 publications
5
23
1
1
Order By: Relevance
“…The study revealed significantly high concentration of Pb from classroom dusts. A report pointed out from a separate study conducted in Nigeria that Pb from most classrooms in their study were well above the limit of 140 g/g set by California Human Health Limits [21,22]. Sources of Pb in the classrooms may be a result of the influence of the winds which can cause quantities of Pb-bearing soil particles from the road sides to be deposited into the classrooms since the windows of the classrooms are usually opened and cleaning may not take place every school day [23].…”
Section: Resultsmentioning
confidence: 99%
“…The study revealed significantly high concentration of Pb from classroom dusts. A report pointed out from a separate study conducted in Nigeria that Pb from most classrooms in their study were well above the limit of 140 g/g set by California Human Health Limits [21,22]. Sources of Pb in the classrooms may be a result of the influence of the winds which can cause quantities of Pb-bearing soil particles from the road sides to be deposited into the classrooms since the windows of the classrooms are usually opened and cleaning may not take place every school day [23].…”
Section: Resultsmentioning
confidence: 99%
“…In urban atmospheres, ambient trace elements typically represent a small fraction of PM 2.5 on a mass basis, while elemental species like Cd, As, Co, Cr, Ni, Pb and Se are considered as human carcinogens even in trace amounts (Iyengar and Woittiez, 1988;Wang et al, 2006;Olujimi et al, 2015). It has been shown that Cu, Cr, Fe and V have several oxidation states that can participate in many atmospheric redox reactions (Litter, 1999;Brandt and van Eldik, 1995;Seigneur and Constantinou, 1995;Rubasinghege et al, 2010a), which can catalyze the generation of reactive oxygenated species (ROSs) that have been associated with direct molecular damage and with the induction of biochemical synthesis pathways (Charrier and Anastasio, 2012;Strak et al, 2012;Rubasinghege et al, 2010b;Saffari et al, 2014;Verma et al, 2010;Jomova and Valko, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Using Equations 2, 3, and 4, the chronic daily intake (CDI) mg/kg/day was used to evaluate exposure to heavy metals in the soil 18,20,21 where, …”
Section: Methodsmentioning
confidence: 99%